Sarcopenia and Frailty in Older Adults in Medellin. SABE Colombia 2015 Survey - Patiño-Villada, Fredy Alonso; Deossa-Restrepo, Gloria Cecilia; Estrada-Restrepo, Alejandro; Benjumea-Rincón, María Victoria (Iatreia, 2024)
Introduction: Sarcopenia and frailty are important medical syndromes affecting the health of older adults. Objectives: To determine the prevalence of sarcopenia and frailty in older adults in Medellín by conducting a secondary analysis of data from the 2015 National Survey on Health, Well-being, and Aging in Colombia (known as SABE Colombia 2015). Methods: Sociodemographic, anthropometric, and health variables in adults ≥60 years were analyzed using the SABE Colombia 2015 data. Sarcopenia was defined according to the European Working Group on Sarcopenia in Older People 2 (EWGSOP2), while frailty was defined using Fried et al.’s phenotype. Binary logistic regression was used to identify factors associated with sarcopenia and frailty. Results: A total of 496 individuals were studied for sarcopenia and 451 for frailty. Sarcopenia was present in 41 older adults (8.3%), while 48 were frail (11.6%). Logistic regression analysis showed that increasing age, lack of formal education, and lower BMI values increase the likelihood of sarcopenia: age (OR 1.08), no formal education (OR 4.4), and BMI (OR 0.66). The factors associated with frailty included age (OR 1.06), no formal education (OR 5.04), and primary education level (OR 4.56). Conclusions: The prevalence of sarcopenia was lower than that of frailty, and both conditions increase with age and lack of formal education. Early detection of these syndromes and timely management will help reduce morbidity and mortality, contributing to healthier aging.